1978
DOI: 10.1042/bj1700219
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cadmium-thionein in isolated rat liver cells

Abstract: The uptake of cadmium by isolated liver cells was linearly related to the cadmium concentration to which the cells were exposed in the medium. Cadmium-treated cells synthesized proteins de novo with the characteristics of cadmium-thionein induced in the liver ofcadmium-treated animals. Thionein from liver cells incorporated cadmium and[35S]cysteine, had a Vl/Vo (Sephadex G-50) of 1.8-1.9, and was separated into two subfractions by DEAE-cellulose ion-exchange chromatography. Cycloheximide and actinomycin D when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The induction of the thionein ligand in animals has been demonstrated in several laboratories after simultaneous administration of 112Cd and 3S or [35S]cysteine (9,13). Similar experiments were performed here with 112Cd and 35S.…”
Section: Discussionsupporting
confidence: 74%
“…The induction of the thionein ligand in animals has been demonstrated in several laboratories after simultaneous administration of 112Cd and 3S or [35S]cysteine (9,13). Similar experiments were performed here with 112Cd and 35S.…”
Section: Discussionsupporting
confidence: 74%
“…In isolated cells exposed to 1 ,ug Cd/ml, cadmium uptake did not vary significantly with time of incubation; however, if the cadmium concentrations were varied metal uptake increased linearly with increasing cadmium concentrations (19). These observations suggested that the cells absorbed the metal by diffusion, an equilibrium was established fairly rapidly after exposure, and the higher the concentration to which cells were exposed, the more metal they absorbed (19).…”
Section: Cadmium Enters Cells and Is Partitioned Between Subcellular mentioning
confidence: 87%
“…The isolation of cadmium thionein and the measurements of cadmium and 35S-cysteine were carried out as described earlier (19,20). and glass-distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that cadmium induces its synthesis by stimulating a specific mRNA synthesis (Squibb and Cousins, 1974;Hidalgo et al, 1978). The immediate effect of cadmium in liver is inhibition of the overall RNA-polymerase activity and protein synthesis (Hidalgo et ai.…”
Section: Introductionmentioning
confidence: 99%